Analysis of The Improvement of Student Self-Efficacy in Grade XI of Vocational High School Through The Discovery Learning Model - Nur Hanipah; Iik Nurhikmayati; Vici Suciawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
The aim of this study is to determine the difference in improving students' self-efficacy between those who use the Discovery Learning teaching style and those who use traditional learning methods. The study included samples from class XI TSM 1 as the experimental group and class XI TSM 2 as the control group. The study utilized purposive sampling as the chosen strategy, which involves gathering data based on specific criteria. The experimental class is exposed to the implementation of the Discovery Learning instructional model, whereas the control class adheres to a conventional learning framework. The results of this study indicate that there is an inequality in the development of self-efficacy between the students in the experimental class and those in the control class. The experimental class saw a considerable enhancement, whereas the control class experienced a minor increase. Therefore, it can be deduced that the experimental class, which employed the Discovery Learning learning model, saw a more significant enhancement in self-efficacy in comparison to the control class that utilized the conventional learning model.